Dominance and Frequency of Coleoptera Found on Stored Cereals and Cereal Products in Central Greece - Buchelos C. Τh.; Athanassiou, C. G. (ENTOMOLOGIA HELLENICA, 1993)
Thirty Coleoptera taxa belonging to 14 families were found during samplings conducted in 4 different storage facilities at Farsala district, Central Greece, from January 1991 to February 1992. Among the most frequently found, Sitophilus oryzae, S. granarius and Rhysopertha dominica were more numerous on grain, Tribolium confusum, T castaneum and Cryptolestes ferrugineus on flour, while Oryzaephilus surinamensis and O. inercator showed no significant preference to any commodity. An analysis of the results was performed, based on the dominance and frequency criteria. The population fluctuation of the 8 most significant species is given in graphs.